Forage cactus (Opuntia ficus-indica (L.) Miller) f. Cactaceae as an alternative for ruminant feeding - Dutra, Ingridy Carvalho; Pires, Aureliano José Vieira; Santos, Brenda Emilly Ferreira dos; Silva, Nadjane Vieira da; Pio, Luanna Pereira; Cruz, Natan Teles; Sousa, Mateus Pereira; Dutra, Geovana de Carvalho (Brazilian Journal of Science, 2024)
The objective of this review was to compile information regarding cacti as an alternative to ruminant feeding. Forage cactus adapts well to soils with low nutrient content, as long as the soil is not acidic, in addition to being tolerant to long periods of drought, since their metabolism is based on crassulacean acids (CAM), thus favoring the use of water and providing high dry mass productivity. Studies have been developed to include cactus in the diet of ruminants, in an attempt to improve consumption by avoiding the occurrence of metabolic disorders in animals. In addition, forage cactus contributes to the intake of colloidal water due to its composition of around 90% water. For forage cactus to be used to feed ruminants, it must be associated with some source of neutral detergent fiber, leading to greater chewing and, consequently, longer rumination time, to guarantee the normal functioning of the rumen, demonstrating improvement in water consumption, digestibility, and animal performance.